ANALISIS STRUKTURAL DAN NILAI MORAL DALAM CERPEN “KEMBANG GUNUNG KAPUR” KARYA HASTA INDRIYANA - Ratih Sapdiani; Imas Maesaroh; Pipin Pirmansyah; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to (1) describe the Interscience of the intrinsic elements of the short story "Kembang Gunung Kapur" by Hasta Indriyana using structural analysis methods, and (2) to describe the moral values contained in the short story, both religious moral and social criticism. The short story "Kembang Gunung Kapur" is examined through data collection steps; (1) to read the short story "Kembang Gunung Kapur" intensively, (2) analyze the integrity of the intrinsic elements of the short story and describe it, then (3) to analyze the moral elements that the author wishes to convey to the short story and to describe it. After going through the process of research structural analysis and moral values, seen effort Hasta Indriyana which combine the elements of the intrinsic short story well, so the message of moral value contained in the short story can reach the reader.